2013
DOI: 10.2478/johh-2013-0034
|View full text |Cite
|
Sign up to set email alerts
|

Time of concentration of surface flow in complex hillslopes

Abstract: Abstract. Time of concentration (TC) of surface flow in watersheds depends on the coupled response of hillslopes and stream networks. The important point in this background is to study the effects of the geometry and the shape of complex hillslopes on the time of concentration considering the degree of flow convergence (convergent, parallel or divergent) as well as the profile curvature (concave, straight or convex). In this research, the shape factor of complex hillslopes as introduced by Agnese et al. (2007)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 32 publications
3
8
0
Order By: Relevance
“…The proportions are similar as used for other larger watersheds. The interflow duration is directly related to the flow path of the water (Sabzevari et al 2013) and has been found to last between the 4 days for simulations of the small watersheds and the 70 days for the Blue Nile Basin at the Sudanese border (Tilahun et al 2013). Our value for the Gilgel Abay of 30 days is therefore reasonable.…”
Section: Physical Analysissupporting
confidence: 53%
“…The proportions are similar as used for other larger watersheds. The interflow duration is directly related to the flow path of the water (Sabzevari et al 2013) and has been found to last between the 4 days for simulations of the small watersheds and the 70 days for the Blue Nile Basin at the Sudanese border (Tilahun et al 2013). Our value for the Gilgel Abay of 30 days is therefore reasonable.…”
Section: Physical Analysissupporting
confidence: 53%
“…By solving the flow dynamic Equations (9)-(14), flow depth, velocity fields on the land surface and the flow discharge from the land surface can be obtained. The computed flow depth and velocity fields are, in turn, used for the erosion dynamics to predict the sediment concentration field on the et al, 2013 andTayfur, 2001 Soil detachability coefficient α kg/m 2 /mm 0.0006-0.0086 for high detachable soils and 0.00012-0.0017 for less detachable soils Foster, 1982;Sharma et al,1993 andTayfur, 2007 Soil erodibility coefficient 6 Foster, 1982;Sharma et al,1993 andTayfur, 2007 land surface and sediment discharge from the land surface (Tayfur, 2001).…”
Section: Solution Proceduresmentioning
confidence: 99%
“…By substituting Equation to this equation, overland flow depth obtains: hx()t=nmanq()tpl()xsx1true/m where n man is the Manning roughness coefficient, s ( x ) is local slope, m is a parameter accounting for flow regimes ( m = 5/3 for turbulent flow, m = 2 for transition flow and m = 3 for laminar flow) (Sabzevari1 et al ., ). Now in order to obtain h x ( t ), the other variables in equation could be solved.…”
Section: Introductionmentioning
confidence: 99%
“…At the pedon scale, soil erosion can be attributed to the separation of soil particles by raindrops and runoff during interrill erosion processes, so preventing this process is an important goal in the management of water and soil resources [6][7][8]. The amount of runoff is a function of navigation time, therefore the accurate estimation of the time of concentration and runoff threshold results in a more accurate hydrograph of flooding [9]. Designing methods and structures for soil water conservation requires accurate estimation of the amount and time of flood peak discharge and time of concentration.…”
Section: Introductionmentioning
confidence: 99%
“…A representative example of this kind of mixed and complex dynamic is the degraded soils of Iran. Since most soils in Iran have low permeability, precipitation exceeds infiltration, hence, surface runoff becomes dominant [9,13].…”
Section: Introductionmentioning
confidence: 99%